Role of panchayats in social development: Excellence in decentralised administration - Palanithurai, G. (2006)
Social development issues are conveniently relegated to the background from public discussion by the political class, and, as a result. India is ranked very low in the Human Development Report. Now issues of social development have been brought to the centre stage for public discussion. The newly created Panchayat institutions have started demonstrating their potential in addressing the key issues of social development in governance at the grassroots which has been perceived as an emerging alternative governance. This article is based on an action research done in 54 Gram Panchayats of Tamil Nadu in four districts on micro planning for social development. - Reproduced.
Keywords: Decentralization; Economic and social development; Panchayat